2009
DOI: 10.1080/17549500903003094
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between prosody and intelligibility

Abstract: In the lead article, Peppé (2009) provides a clear and detailed overview of prosody as it relates to the field of speech-language pathology, an often marginalized and misunderstood subject. Peppé makes a convincing case as to why speech-language pathologists should take notice of atypical prosody in the speech of their clients and provides an overview of current methods of documentation. Peppé also briefly notes that prosody can affect intelligibility and the purpose of this article is to expand upon this poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…An understanding of vocal production in ASD is important because acoustic abnormalities may play a role in the social‐communicative impairments associated with the disorder [Depape et al, ; Klopfenstein, ]. For example, individuals with ASD have difficulties with the communication of affect [Travis & Sigman, ] – which relies on the production of prosodic cues – leading to negative social judgments on the part of others [Fay & Schuler, ; Paul et al, ; Shriberg et al, ; Van Bourgondien & Woods, ] and in turn social withdrawal and social anxiety [Alden & Taylor, ].…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of vocal production in ASD is important because acoustic abnormalities may play a role in the social‐communicative impairments associated with the disorder [Depape et al, ; Klopfenstein, ]. For example, individuals with ASD have difficulties with the communication of affect [Travis & Sigman, ] – which relies on the production of prosodic cues – leading to negative social judgments on the part of others [Fay & Schuler, ; Paul et al, ; Shriberg et al, ; Van Bourgondien & Woods, ] and in turn social withdrawal and social anxiety [Alden & Taylor, ].…”
Section: Introductionmentioning
confidence: 99%
“…Today, the majority of existing blind measures depend on quantifying atypical prosody and parameters such as fundamental frequency (f0) variation and second-formant slope transitions [6]. Recent studies, however, have shown that articulation errors are the major contributing factor to reduced intelligibility in dysarthric speech [7], followed by prosody, voice quality, and nasality.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of rigidity of speech musculatures and reduced range of articulatory movements, speech associated with PD is generally characterized by monopitch, inappropriate pitch level, reduced stress, monoloudness, inappropriate silences, short rushes of speech, variable speech rate, harsh and breathy voice qualities [2], all could have direct and/or indirect impact on speech prosody. Impairment in speech prosody not only affects the expression of linguistic intonations and emotions; but is also reported to negatively influence overall intelligibility [3,4], and may thus result in reduced communication efficiency and listeners making negative personality judgement about the speakers [5]. However, only very few studies have explored the effects of impaired speech prosody on intelligibility, indicating that prosody might be the second most impacting factors on speech intelligibility, after articulation [3].…”
Section: Introductionmentioning
confidence: 99%